2020
DOI: 10.1038/s41598-020-76677-z
|View full text |Cite
|
Sign up to set email alerts
|

Hemocytes released in seawater act as Trojan horses for spreading of bacterial infections in mussels

Abstract: Global warming has been associated with increased episodes of mass mortality events in invertebrates, most notably in bivalves. Although the spread of pathogens is one of multiple factors that contribute to such mass mortality events, we don’t fully understand the pathophysiological consequences of sea warming on invertebrates. In this work, we show that in temperature stress conditions, circulating hemocytes in mussels leave the hemolymph to gain access to the intervalvar fluid before being released in seawat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Noteworthy, the mussels in the Gaydamak Bay were collected from the surface of a mooring buoy in a heavily polluted area, where no mussels were recorded at the sea floor (our observations). Since BTN is presumably transmitted by cancer cells through the water column (see Caza et al 72 for more discussion), we suspect that the mussels fouling the buoy contracted the infection from those that had fouled ships moored to it. We point out that mussel populations on mooring buoys, docks etc.…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the mussels in the Gaydamak Bay were collected from the surface of a mooring buoy in a heavily polluted area, where no mussels were recorded at the sea floor (our observations). Since BTN is presumably transmitted by cancer cells through the water column (see Caza et al 72 for more discussion), we suspect that the mussels fouling the buoy contracted the infection from those that had fouled ships moored to it. We point out that mussel populations on mooring buoys, docks etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a permanent cell exchange between hemolymph and intravalvular fluids in bivalves. Recently, Caza et al 43 showed that under temperature stress conditions, circulating hemocytes were able to leave the hemolymph to gain access to the intervalvular fluid before entering other mussels. Therefore, hemolymph is a likely route for the leakage of cancerous cells outside the infected host.…”
Section: Discussionmentioning
confidence: 99%
“…Although empirical evidence is currently lacking to support the hypotheses outlined above, future transfection experiments could prove or disprove these theories. For example, mussels have a natural tendency to open their valves and to release and uptake hemocytes ( Caza et al, 2020 ). Placing mussels under different environmental conditions and exposing them to stained BTN cells (e.g., CFSE, a cytosol dye commonly used for tracking cells in vivo by flow cytometry), followed by transcriptome and epitome analyses of both established BTN and host cells may reveal the phenotypic composition of BTN cells that were successfully taken up by and survived in the new host ( Caza et al, 2020 ).…”
Section: Group Phenotypic Composition In the Context Of Cancermentioning
confidence: 99%